1996
DOI: 10.1021/jp950999q
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Denaturation Process in Albumin−Urea Solutions by Means of the Thermally Stimulated Depolarization Currents Technique

Abstract: The dielectric relaxation of bovine serum albumin (BSA) aqueous solution was studied in various stages of urea denaturation by means of the thermally stimulated depolarization currents (TSDC) technique. A large variation of urea concentration was utilized (0-4 M). Special attention was given for concentrations between 0.006 and 0.050 M, which are comparable to those measured in normal and uremic human serum. The TSDC spectrum consists of two main bands in the temperature range 100-300 K: (1) a broad low-temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Vassilikou-Dova et al [385] studied the dielectric relaxation of bovine serum albumin (BSA) in aqueous solution with various stages of urea denaturation by the TSDC technique. A large variation of urea concentration was utilized (0-4 M).…”
Section: Bio-moleculesmentioning
confidence: 99%
“…Vassilikou-Dova et al [385] studied the dielectric relaxation of bovine serum albumin (BSA) in aqueous solution with various stages of urea denaturation by the TSDC technique. A large variation of urea concentration was utilized (0-4 M).…”
Section: Bio-moleculesmentioning
confidence: 99%
“…It has been used for the study of myoglobin, lysozyme, RNase, and Binase. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] In this work, we compare the dynamic behaviors of native and hydrophobized GOx by the TDDS method, and we evaluate the effect of the attachment of hydrophobic groups to the protein molecule on its structure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the application of time-domain dielectric spectroscopy (TDDS) has been successful in obtaining new information on the structural and dynamic parameters of protein globules in conformational transitions induced by temperature and pH changes. It has been used for the study of myoglobin, lysozyme, RNase, and Binase. …”
Section: Introductionmentioning
confidence: 99%